Effect of Processing on Viscosity and Molecular Weight of (1, 3)(1, 4)‐β‐Glucan in Western Australian Oat Cultivars. Issue 3 (23rd January 2017) - Mitra, Sabori; Lahnstein, Jelle; James, Anthony P.; Fenton, Haelee K.; Burton, Rachel A.; Cato, Larisa; Solah, Vicky A.
Abstract : Six Australian milling oat cultivars grown over two growing seasons were characterized for differences in (1, 3)(1, 4)‐β‐glucan (β‐glucan) viscosity, solubility, molecular weight (Mw ), and the effect of processing. Oat cultivars grown in 2012 had significantly higher extracted β‐glucan viscosity from oat flour than the same oat cultivar grown in 2011 ( P < 0.05, mean 137 and 165 cP, respectively). Noodle β‐glucan mean viscosity for 2012 (147 cP) was significantly higher than for 2011 (128 cP). β‐Glucan from 'Williams' and 'Mitika' oats had the highest viscosity ( P < 0.05) in flour (5.92 and 5.25%, respectively) and noodles (1.64 and 1.47%, respectively) for both years, compared with the other oat cultivars. β‐Glucan (Mw ) of Williams for 2012 and 'Kojonup' for both years were the least affected by processing, with an average drop of 33% compared with a maximum of 63% for other cultivars. Therefore, Williams showed superior β‐glucan properties to other oat cultivars studied, and can potentially provide improved health benefits. High and low β‐glucan Mw populations were found in the same elution peak after processing. Oat cultivars chosen for processing should be those with β‐glucans that are more resistant to processing, and that maintain their physiochemical properties and, therefore, bioactivity.